Strategic leadership in a dressed economy - Nhuta, Stephen (International Journal of Research in Management, Economics & Commerce, 2016)
A paper prepared and presented by Dr Stephen Nhuta (Midlands State University) at the “Update on current affairs seminar” by the Institute of Chartered Secretaries and Administrators in Zimbabwe